KEBIJAKAN GASTRODIPLOMASI JEPANG DI INDONESIA (2013-2014) - Marco Julio Hotnaldy Pasaribu, (2022)
This study aims to discuss the significance of Japanese gastrodiplomacy policies in Indonesia in the period 2013 to 2014 for Japan. Japan is a country that is famous for it's world-famous food, sushi, sashimi and ramen are just a few of the many Japanese specialties that are popular throughout the world, including in Indonesia. The popularity of Japanese food is inseparable from the active role of the Japanese government in introducing Japanese specialties through gastrodiplomacy. Indonesia is one of Japan's gastrodiplomacy destinations. In 2013, Japan launched it's halal food development program under the name Japan Halal Food Project. Through the Japan Halal Food Project program, Japan seeks to strengthen bilateral relations between Japan and Indonesia, especially in the field of halal food products, expand and improve halal food in the Japanese food industry and also spread Japanese cuisine throughout the world. In it's implementation, Japan introduced the Japan Halal Food Project program by building relationships through the media, holding a Cooking Japan School Caravan event, presenting the Cooking Japan booth at the Indonesia-Japan Expo 2013 and holding product seminars and business matching. The method used in writing this thesis is a qualitative research method using secondary data. Data collection techniques were carried out through the documentation method. The author uses three stages of data analysis according to Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. In writing this thesis, the author uses the concept of gastrodiplomacy and the theory of public diplomacy. The main conclusion from this thesis is that the Japanese gastrodiplomacy policy carried out in Indonesia through the Japan Halal Food Project program provides significance in the form of increasing Japanese restaurants in Indonesia, increasing the number of Indonesian tourists to Japan and increasing halal restaurants and food in Japan. Keywords : Japan, gastrodiplomacy, public diplomacy, Japan halal food project, halal